2014
DOI: 10.1016/j.yjmcc.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the development of the electrocardiographic and arrhythmic manifestations of early repolarization syndrome

Abstract: Background Early repolarization pattern in the ECG has been associated with increased risk for ventricular tachycardia/fibrillation (VT/VF), particularly when manifest in inferior leads. This study examines the mechanisms underlying VT/VF in the early repolarization syndrome (ERS). Method Transmembrane action potentials (AP) were simultaneously recorded from 2 epicardial and 1 endocardial site of coronary-perfused canine left-ventricular (LV) wedge preparations, together with a pseudo-ECG. Transient outward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
124
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 45 publications
11
124
1
2
Order By: Relevance
“…16,23,[33][34][35] Some controversy exists as to whether the electrocardiographic findings represent ER, late depolarization, or neither. 36,37 The repolarization hypothesis suggests that the presence of the ERP reflects regional heterogeneity in the dispersion gradient of myocardial refractoriness prompted by a net outward shift in repolarizing current.…”
Section: Biological Basis and Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,23,[33][34][35] Some controversy exists as to whether the electrocardiographic findings represent ER, late depolarization, or neither. 36,37 The repolarization hypothesis suggests that the presence of the ERP reflects regional heterogeneity in the dispersion gradient of myocardial refractoriness prompted by a net outward shift in repolarizing current.…”
Section: Biological Basis and Geneticsmentioning
confidence: 99%
“…23 Meticulous studies of canine left ventricular wedge preparations have shown accentuation of the action potential notch in the epicardium enhanced by vagal tone, associated with increased level of I to current, and reversed by quinidine and isoproterenol, supporting the repolarization hypothesis. 35 The depolarization hypothesis proposes that slowed conduction in the right ventricular outflow tract with fractionated and late potentials contributes to arrhythmogenicity. 38 Several observations have raised speculation that a genetic basis for ERP exists.…”
Section: Biological Basis and Geneticsmentioning
confidence: 99%
“…5 They suggested that vagal activity contributes to the arrhythmogenicity in ER and J-wave syndrome patients.…”
Section: Discussionmentioning
confidence: 99%
“…50 Recent studies have provided insight into how the repolarization gradients in ER translate into arrhythmogenesis. 51 The study by Koncz et al 51 suggest that the AP dome of cells within LV epicardium become accentuated giving rise to phase 2 reentry and PMVT. This study showed that repolarization defects can be accentuated by acetylcholine, explaining the deleterious influence of elevated vagal tone, and that relatively high intrinsic levels of I to account for the greater sensitivity of the inferior LV wall to development of VT/VF.…”
Section: Mechanism Of Arrhythmiamentioning
confidence: 99%